Mathematical and engineering methods in computer science : 10th International Doctoral Workshop, MEMICS 2015, Telč, Czech Republic, October 23-25, 2015, Revised Selected Papers /: 10th International Doctoral Workshop, MEMICS 2015, Telč, Czech Republic, October 23-25, 2015, Revised Selected Papers. (2016) - Unknown
No abstract available